ASSA13-08-8 Features and Treatments of Hypertension in Elderly Patients with Stanford B Aortic Dissection. (29th April 2013) - Mingyu, Sun; Xiaozeng, Wang; Quanmin, Jing; Zulu, Wang; Yaling, Han
Abstract : Objective: To summarise the features and treatments of hypertension in elderly patients with Stanford B aortic dissection. Methods: Retrospectively analysed the features and treatments of hypertension between the elderly patients (≥ 60 years, n = 91) and the non-elderly patients (n = 187) who were suffered from Stanford B aortic dissection and hospitalised between April 2002 and July 2011. Results: The proportion of male in elderly group was higher than that in non-elderly group ( P < 0.05). Smoking was similarly common in both groups. The proportions of patients accompanied with diabetes mellitus, hyperlipidemia, hypertension and renal inadequacy had no statistics differences between two groups. Coronary artery disease, atherosclerotic ulcer and cardiac insufficiency were more often seen in elderly group ( P < 0.05). Histories of hypertension were more often given while the first-time diagnosis of hypertension were made less frequently in elderly group ( P < 0.05). Isolated systolic hypertensions were seen with greater frequency in the elderly group ( P < 0.05). The courses of hypertension were longer in the elderly group than those in the non-elderly group ( P < 0.05). The proportions of family history of hypertension and hypertension of grade 1, grade 2 and grade 3 had no statistics differences between two groups. The highest systolic pressures, diastolic pressures and pulse pressures of the patients on admission and the average systolic pressures, diastolic pressures and pulse pressures after treatments had no statistics differences between two groups. The combined treatments were applied frequently in both groups. The usages of intravenous drugs had no differences between two groups. Combinations of 2 antihypertensive drugs were more often used in the elderly group than those in the non-elderly group ( P < 0.05). Combinations of 3 antihypertensive drugs were used most frequently in both groups. Calcium-channel blocker, β-receptor blocker, angiotensin-converting enzyme inhibitor, angiotensin receptor blocker, diureticum, angiotensin receptor blocker+diureticum and α1 + β receptor blocker were adopted in turn as hypotensive drugs in elderly group. α1 + β receptor blocker was less used in the elderly group ( P < 0.05). Conclusions: The awareness rate of hypertension was higher and the highest blood pressures on admission were lower in elderly patients with Stanford B aortic dissection. The types of anti-hypertension drugs were less and α1 + β receptor blocker was less used in the elderly group.